THE IMPACT OF COVID-19 PANDEMIC ON THE INDIAN INSURANCE MARKET AND CONSUMER ATTITUDES TOWARD HEALTH INSURANCE (International Journal of Food and Nutritional Sciences, 2022)
Insurance Industry significantly contributed to India’s economic progress, by offering risk coverage, investment opportunities, and tax planning for individuals. Life Insurance offers many benefits to people, while non-life insurance policies offer risk coverage for possessions like real estate, cars, and other assets. In March 2020, fast spread of the coronavirus resulted in declaring lockdown, and all industries have been forced, to rethink how they conduct business, and the insurance sector is no different from this. Everyone working from home, some employees' salaries were withheld, while others lost their employment. The aim of this study was to examine the benefits of insurance and the impact of the COVID-19 pandemic on the insurance industry. Furthermore, a research was focused on how customers perceived insurance during the Covid-19 period, the Lockdown, and the consequence of the pandemic on the selling of insurance policies.